The importance of export of Ukrainian confectionary products - Udvorheli, Christina (My University, 2014)
The confectionary sector is one of the most intensive and advanced sectors within the food industry. It is resistant to economic downturns and confectionery products continue to enjoy steady demand. Since the volume of domestic consumption of confectionary products is sustainable in the medium term, and domestic demand for confectionary products is almost entirely met by national producers, increasing production is possible through increasing exports. This fact is very important for increasing enterprises income and GDP.
Keywords: confectionary products; food industry; export; кондитерские изделия; пищевая промышленность; экспорт; кондитерські вироби; харчова промисловість; експорт; кафедра економіки праці та менеджменту